Implementasi Strategi Mengalami, Interaksi, Komunikasi dan Refleksi (Mikir) dalam Meningkatkan Hasil Belajar Matematika Siswa Madrasah Ibtidaiyah - Susanti, Dyah Aris (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
The research aims to understand the planning or scenario of the MIKiR learning strategy in the mathematics subject for fourth-grade students at MIS Roudlotun Nasyiin Udanawu and the contribution of implementing and the results of the MIKiR strategy in improving mathematics learning outcomes. This research adopts a qualitative approach. The study type used in this research is a case study with data collection techniques including observation, documentation, and interviews. The results indicate that the planning or scenarios, including models, media, and methods used in teaching fourth-grade students at MIS Roudlotun Nasyiin Udanawu, are appropriate and tailored to students' needs and the theme/material. The implementation and results of the MIKiR strategy contribute to the mathematics learning process, enhancing students' learning outcomes in cognitive (knowledge), affective (attitude), and psychomotor (skills) aspects after participating in mathematics learning using the Experiencing, Interacting, Communicating, and Reflecting (MIKiR) strategy.